2019
DOI: 10.1177/1356766719867374
|View full text |Cite
|
Sign up to set email alerts
|

Customer orientation and SME performance in Albania: A case study of the mediating role of innovativeness and innovation behavior

Abstract: Although the tourism industry in Albania has had an impressive growth in the last years, it is currently facing several challenges. This study examines the determinants of Albanian tourism small and medium-sized enterprise (SME) performance. More specifically, the direct effects of customer orientation (CO) on performance and its indirect effects mediated by innovativeness and innovation behavior are investigated. Quantitative data from a survey conducted on 211 Albanian tourism SMEs, together with qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 86 publications
3
37
3
1
Order By: Relevance
“…The results of hypothesis testing explain that marketing innovation and marketing performance have a positive and significant relationship, these results support research conducted by (Domi & Musabelliu, 2019), (Kijkasiwat & Phuensane, 2020), (Soto-acosta et al, 2015), and (Ashrafi & Ravasan, 2018). That is, with the MSME marketing sector, this has a good impact on its marketing performance.…”
Section: Relationship Between Marketing Innovation and Marketing Performancesupporting
confidence: 77%
See 1 more Smart Citation
“…The results of hypothesis testing explain that marketing innovation and marketing performance have a positive and significant relationship, these results support research conducted by (Domi & Musabelliu, 2019), (Kijkasiwat & Phuensane, 2020), (Soto-acosta et al, 2015), and (Ashrafi & Ravasan, 2018). That is, with the MSME marketing sector, this has a good impact on its marketing performance.…”
Section: Relationship Between Marketing Innovation and Marketing Performancesupporting
confidence: 77%
“…Marketing performance is a measure of marketing success achieved, by matching marketing with output in terms of net profit, market share, sales growth within a certain period (Wali & Opara, 2012). Marketing performance is an evaluation of the achievement of marketing objectives related to the vision, mission, and marketing objectives in the period under review (Fred Wali et al, 2015) This is also supported by research which explains that innovation also has a significant effect on the performance of MSMEs (Domi & Musabelliu, 2019), (Kijkasiwat & Phuensane, 2020), (Soto-acosta et al, 2015), and (Ashrafi & Ravasan, 2018). Research findings Oke et al (2007) show that there is a relationship between innovation and SME sales turnover growth.…”
mentioning
confidence: 98%
“…Since the end of the 20th century, China's economic and social transformation, entrepreneurship, and innovation economy have become the strategic focus of future development, and also the focus of many scholars. Domi et al (2020) found in their survey of 211 Albanian tourism SMEs that innovation and innovation behaviors play an intermediary role in the relationship between enterprise synergy and performance. Kurniawan et al (2020) conducted a questionnaire survey on 150 enterprise personnel in the creative industry and found that there was a significant positive correlation between knowledge sharing and absorptive ability and creative and innovative ability (p < 0.05).…”
mentioning
confidence: 99%
“…In order to have less ambiguous questions, we did have a preliminary test with academics (see e.g. Domi et al, 2020;). In addition, to assess the clarity and understandability of the measures we made a pre-test of the questionnaire with some citizens that did recently utilize service of the public sector.…”
Section: Methodsmentioning
confidence: 99%